A compact multifunctional metastructure for Low-frequency broadband sound absorption and crash energy dissipation. (March 2022) - Ren, Zhiwen; Cheng, Yuehang; Chen, Mingji; Yuan, Xujin; Fang, Daining
Graphical abstract: Highlights: A novel compact multifunctional metastructure is proposed for both low-frequency broadband sound absorption and excellent crash energy dissipation. An optimization method, resisting degradation from impedance coupling effect, contributes to flatter and higher sound absorption coefficient curves. The as-designed metastructure with deep-subwavelength thickness exhibits quasi-perfect broadband sound absorption performance. The as-designed metastructure is verified to have the same superior load-bearing and crash energy dissipation performance as an intact honeycomb structure. Abstract: Sound absorption structures, as an effective approach to reducing sound radiation, have always received extensive attention in the engineering of vibration and noise reduction. In this work, a novel compact multifunctional metastructure is proposed for both low-frequency broadband sound absorption and excellent crash energy dissipation. Cavity resonators with internally extended tubes (CRIET) with hexagonal honeycomb configuration were selected as unit components. An optimization method was proposed to against degradation from impedance coupling effect and contribute to flatter and higher sound absorption coefficient (SAC) curves. The as-designed metastructure has been demonstrated experimentally to have quasi-perfect broadband sound absorption in the target range of 600–1000 Hz with an average SAC above 0.9 and a deep-subwavelength thickness of 30 mm. Compression experiment showed that the CRIET metastructure with hexagonal honeycomb configuration had the same unique excellent load-bearing and crash energy dissipation performance as an intact honeycomb structure. This study provides inspirations and methods for the compact and multifunctional design of broadband sound absorption structures.